Penilaian Kinerja Guru dengan Model Fuzzy Multi Atribute Decision Making Saw pada SMA Unity School - Malau, Yesni; Juando, Raden Rivan; Adiwiharja, Cep (JUSS (Jurnal Sains dan Sistem Informasi), 2018)
This article content abaut the implementation abaut work examination of teachers performance at Unity School High School The process of examination will determine the extension of the teaching contract and as a reference for increasing teachers salaries. The number of subject teachers and the skills of each teacher are varies making decision to apraise the performance of Teachers at Unity School High School are still confused. This time the work examination of teachers performance at Unity School High School appraisal is only the attendance of teacher teaching and personal assessment from the Director of Education during interviews. Unity School High School needed of decision support system for work examination of teachers performance, a decision support system that can determine the calculation values for all criteria. Simple Additive Weighting (SAW) method is a method that looks for weighted sums, there are eight criteria use are student understanding, behavior, initiative, integrity, collaboration, discipline, mastery of teaching material, and delivery of material to students. In this case the teacher's performance assessment is done by summing the weights of the values in each alternative for all attributes. Larger values will indicate that the alternative is selected.